Development of Electronic Worksheet Assisted by Augmented Reality to Improve Learning Outcomes and Interest in Learning Science - Andista Candra Yusro; Muhammad Zaki Ramadhani; Nining Tin Wayuni (IKIP Mataram, 2023)
This research aims to: 1) produce feasible and valid electronic worksheets assisted by augmented reality that can be used to improve learning outcomes and interest in learning science; and 2) know the effectiveness of electronic worksheets assisted by augmented reality to improve learning outcomes and interest in learning science. This study used 4D model R&D research. The research was conducted in SMP Madiun City with class VIII research subjects totaling 17 students. Data collection instruments include product validation and feasibility tests, pretest and posttest questions, and learning interest questionnaires. Data analysis techniques using paired T-tests. The results obtained from the material validation tests were 63 in the interval 72 ≤X ≥58.5 criteria with a very good category, while the results from the media validation tests were 65,25 in the interval 68 ≤X ≥55,25 criteria with a very good category. Based on the results of the student response questionnaire, a percentage of 68.35 in the interval 84≤X ≥68.25 criteria indicates a very good category and is suitable for use. The results of testing learning outcomes and interest in learning science with paired T-tests obtained results of 0.007 and 0.005, indicating that there were differences in learning outcomes and interest in learning science after using electronic worksheets assisted by augmented reality. Thus, it can be said that 1) electronic worksheets assisted by augmented reality have met the eligibility criteria with a very good category according to material experts and media experts, and 2) electronic worksheets assisted by augmented reality are effective in improving learning outcomes and interest in learning science.